Digital Games and Cultural Dynamics: An Examination of The Social and Cultural Impacts of Popular Games in Türkiye Through Steam - Tamer Bayrak (İletişim Kuram ve Araştırma Dergisi)
This study examines the genres and themes of the most purchased games in Türkiye on the Steam platform from 2021 to 2024, addressing the influence of these games on users' cultural preferences and social values. For this purpose, the top 10 best-selling games in Türkiye were tracked on the Steam platform during January, February, March, April, May, and June 2024. Additionally, the top 50 best-selling games overall from 2021, 2022, and 2023 were analyzed under various categories. These data were evaluated individually and collectively to understand how games function as cultural carriers. The research incorporates content analysis, data collection, and comparative analysis methods within the framework of cultural studies. It analyzes how the themes, characters, stories, and gameplay mechanics reflected in the game content interact with social norms, values, and behaviors within the context of genres and themes. Strategy games, particularly popular among young people, enhance critical thinking and problem-solving skills. Historical-themed games foster a sense of national values, and competitive games strengthen teamwork and leadership skills. Furthermore, interaction with global cultures through games can broaden young people's worldviews and build bridges between different cultures. The analyses conducted in this context demonstrate that games are not only tools for passing time but also powerful cultural instruments capable of influencing social norms, values, and behaviors. The research findings reveal that digital games play a significant role in shaping the representation of concepts such as gender, race, nationality, and class, and in the construction of cultural identities.